Transformation of education as the most important factor in the development of the economic society of Uzbekistan - Miralieva Dilafruz Tahirovna (Zien Journals, 2023)
Today, in the economic development of Uzbekistan, the processes of transformation and development of the digital economy are considered topical issues. Transformation (lat. transformatio - change, adaptation) is the process of development of the world economy, the ability of society to adapt to new conditions.
Keywords: Uzbekistan; economic development